Differential impact of unrecognised brain infarction on stroke outcome in non-valvular atrial fibrillation - Song, Tae-Jin; Kim, Jinkwon; Lee, Hye Sun; Nam, Chung Mo; Nam, Hyo Seok; Kim, Eun Hye; Lee, Ki Jeong; Song, Dongbeom; Heo, Ji Hoe; Kim, Young Dae (Thrombosis and Haemostasis, 2014)
There has been little information regarding the impact of unrecognised brain infarctions (UBIs) on stroke outcome in patients with nonvalvular atrial fibrillation (NVAF). By using volumetric analysis of ischaemic lesions, we evaluated the potential impact of UBIs on clinical outcome according to their presence and categorised type. This study enrolled 631 patients with NVAF having no clinical stroke history. UBIs were categorised into three types as territorial, lacunar, or subcortical. We collected stroke severity, functional outcome at three months, and the total volume of UBIs and acute infarction lesions. We investigated the association between clinical outcome and the type or volume of UBI, using a linear mixed model and logistic regression analysis. UBIs were detected in 285 (45.2 %) patients; territorial UBIs were observed in 24.4 % of patients (154/631), lacunar UBIs in 25 % (158/631), and subcortical UBIs in 15.7 % (99/631). Although initial stroke severity was not different between patients with UBIs and those without, those with UBIs had less improvement during hospitalisation, leading to poorer outcome at three months. Among the three types of UBIs, only territorial UBIs were associated with poor outcome, especially in patients with relatively smaller acute infarction volume. UBIs, in particular, territorial UBIs, may be considered as predictors for poor outcome after ischaemic stroke in patients with NVAF. Our results suggest that the impact of UBIs on clinical outcome differs according to the type of UBIs and the acute stroke severity.
Keywords: Unrecognised brain infarction; non-valvular atrial fibrillation; outcome